Potencial evocado miogênico vestibular cervical e vídeo-teste do impulso cefálico na doença de Ménière - Grigol, Thais Alvares De Abreu E Silva [UNIFESP] (2018)
Objectives: To describe the results of the Cervical Vestibular Evoked Myogenic and VideoHead Impulse Test in patients diagnosed with Definite Ménière's Disease and to correlate with the disease duration. Methods: The sample was constituted of 50 participants, of which 29 were the study group and 21 were the control group. The patients were submitted to a questionnaire, otoscopy, audiometry and vestibular function assessment through Cervical Vestibular Evoked Myogenic and Video Head Impulse Test. Results: For Video Head Impulse Test, the lateral canal gain values below 0.77 were considered altered and for the vertical channels below 0.61; the percentages of normality were 82.76% lateral, 89.65% posterior and 91.37% anterior. For Cervical Vestibular Evoked Myogenic Potential, the upper limits of the latencies were 18.07ms for p13 and 28.47ms for n23; 19.57% prolongation of p13 and 4.35% of n23 and 20.68% were absent. Conclusions: For Video Head Impulse Test a decreased gain of the vestíbuloocular reflex for the lateral canal, with a higher incidence of overt type corrective saccades in comparison with the control group. For Cervical Vestibular Evoked Myogenic Potential, there was a significant difference between the groups for the Interamplitude parameter, including for asymptomatic ear. There was no correlation between the results of the tests with the disease duration.